On What Side of Praxis? U.S. Ethnic Studies, The Global Horizon, and The Problem of Theory Through an Asian American Lens - Fusco, Serena (Status Quaestionis, 2024)
This essay historicizes U.S. ethnic studies, especially focusing on the Asian American component of the field. Besides illuminating dynamics that are shared by the whole spectrum of ethnic studies, an Asian American “lens” offers an opportunity for “zooming in” and reflecting on some meaningful, productive “tensions” that, in turn, highlight the broader relevance and potential of an “ethnic” perspective. I shall argue that the oscillation between the local and global dimensions of the Asian American field; the historically pivotal role of literary studies and literary teaching for Asian America; and a long history of entwinement between academic institutionalization, theoretical elaboration, and political, socially transformative energies, constitute recurrences in Asian American studies that, once historicized, can prove their importance for us today beyond strict field compartimentalizations. Specifically, I suggest that this history can offer food for thought for recent Comparative literature approaches that wish to deploy a world perspective; and that it can constitute an interesting case study for reflecting on theory as inextricably linked with praxis as well as on the relationship between academic institutions and their “outsides” – a reflection that we especially need nowadays.